Pelindungan Data Pribadi Nasabah di Era Open Banking (Studi Komparasi di Indonesia dan Inggris) - Adinda Rizky Fajri (Universitas Sebelas Maret, 2024)
This study compares the customer personal data protection in the era of open banking between Indonesia and the United Kingdom. Open banking, which allows banks to share customer financial data and information with third parties via API, offers ease of access and innovation in financial services. In Indonesia, the implementation of open banking is initiated by Bank Indonesia through the National Standard for Open API Payments. Meanwhile, the UK has adopted open banking since 2018 with legal frameworks such as the Payment Service Directives (PSD2) and General Data Protection (GDPR), which emphasize personal data protection and financial market openness. The research method used is normative juridical with regulatory and comparative approaches. The results show that the UK’s success in implementing open banking that has specific implementation and supervisory entity namely OBL, can serve as a lesson for Indonesia to create strong legal certainty in personal data protection, which in turn will enhance consumer trust and the development of the digital financial sector.